Моделі регулювання природних монополій - Фастова, Н. І. (ХНУРЭ, 2014)
The works is devoted to USA, UK and France experience of natural monopolies regulation. The government regulatory policy, models of regulation and specific instruments of regulation are in focus.
Keywords: регулювання природних монополій; монополії